I saw the TV glow [videorecording (Blu-Ray)] - Schoenbrun, Jane; Smith, Justice, 1995-; Lundy-Paine, Brigette, 1994-; Howard, Helena, 1998-; Jordan, Lindsey, 1999-; O'Malley, Connor, 1986-; Foreman, Ian; Durst, Fred, 1971-; Deadwyler, Danielle; Yue, Eric; Sandy Alex G., 1993- (A24, 2024)
Teenager Owen is just trying to make it through life in the suburbs when his classmate introduces him to a mysterious late-night TV show, a vision of a supernatural world beneath their own. In the pale glow of the television, Owen's view of reality begins to crack.